The Analysis Of Semantics Meaning Found In Comments Of Instagram Account Of Infosumbar Based On Leech’ Theories (Conference on English Language Teaching, 2023)
The aim of this study was to categorize the variety of meanings in semantics found on social media, particularly on Instagram accounts. The phrases, clauses, andsentences found in the comments on the Instagram account Infosumbar serve as the study's source of data. According to Leech's theory, this research focuses on seven different semantic meaning types. This study uses a descriptive qualitative methodology. The observation approach is the one employed to collect data for this investigation. According to the research, five different forms of semantic meaning— conceptual meaning, connotative meaning, social meaning, reflective meaning, and collocative meaning—were present in the comments on the Infosumbar Instagram account.  Social  meaning  is  the  most  common  type  of  meaning  (43.70%).  Within specific contexts of society, social meaning helps in language interpretation and understanding. We may better understand the intended messages and prevent misunderstandings by taking into consideration the social meanings of words and expressions.